Spatial planning concept for flood prevention in the Kedurus River watershed - Susetyo Cahyono; Yusuf Lukman; Setiawan Rulli Pratiwi (Open Geosciences, 2022)
The phenomenon of urbanization has led to an increase in residential land and other economic activities that resulted in the conversion of undeveloped land into developed and settled lands. Thus, it has an impact on limited water absorption, and eventually, a flood occurs when extreme rainfall happens. The Kedurus watershed is a flood-prone area where floods consistently occur with a depth of up to 1 m. However, the Kedurus watershed is an area that has a vital function in the economic development of the city of Surabaya. From the previous research, three instruments were declared effective in reducing flooding. By using the positivistic approach, the purpose of this study is a spatial planning concept for flood reduction in the Kedurus River Basin. The results will be presented as spatial modeling of the flood with the existing conditions resulting in a flood inundation area of 228.88 ha. The stages of the formulation of the spatial planning concept for flood reduction resulted in several proposals, namely, the allocation of green open space for all the land assets of the Surabaya City government and the provision of a maximum requirement of 60% development for space allocation on existing nondeveloped land.